Increased glycolysis as protective adaptation of energy depleted, degenerating human hibernating myocardium - Vogt, Achim; Elsässer, Albrecht; Nef, Holger M.; Bode, Christoph; Kübler, Wolfgang; Bäumner, Jutta (Molecular and cellular biochemistry, 2003)
In the current study on human hibernating myocardium (HHM), we tested the hypothesis that increased glycolysis might exert a positive effect during a supply-demand balance situation by augmentation of myocardial energy formation. In 14 patients HHM was preoperatively detected by clinical methods and validated by the recovery of contractile function three months following revascularization. During open-heart surgery, transmural biopsies were removed from the hibernating areas and analyzed using biochemical and morphologic methods. Metabolite contents were normalized for the degree of fibrosis (control: 9.8 ± 0.5%, HHM 28.1 ± 3.0%; p < 0.05), providing values for cardiomyocytes only. In energy depleted HHM, severe intracellular degeneration, glycogen accumulation and myocyte loss were found. Elevated lactate levels (2.22 ± 0.26 vs. 25.38 ± 3.53 μmol/wet wt, p < 0.001) were indicative of an increased anaerobic glycolytic flux. In conclusion the presence of abundant intracellular glycogen and an increased anaerobic glycolysis in HHM is indicative of a protective adaptation of this myocardium, which might balance energy deficit and may limit structural damage.
Gesehen am 18.06.2021